Public common-sense assumptions about mathematics - Jasmine Y. Ma; Arundhati Velamur; Nurdan Turan; Ali R. Blake; Lauren Vogelstein; Molly L. Kelton; Wendy Barrales (Prometeica)
Circulating public discourses about mathematics and mathematics learning shape how families and students make sense of their experiences with schooling. In the United States, these discourses can play a large role in how public education policy is developed due to the commitment of public school boards to hearing community voices as well as a recent (but not new) increase in the organization of well-funded conservative parent groups working to maintain–and exacerbate–the inequitable educational opportunities that persist in this country. In this paper we analyze public discourse around mathematics learning in one New York City local school board meeting. Using tools from interaction analysis, we examined the discourse surrounding a proposal to reinstate test-based screening for middle school admissions. We delineated two key features of “common-sense” assumptions around mathematics learning that circulated in this meeting–math learners stay on a one-dimensional learning trajectory, and with varying rates of advancement–and investigated how these assumptions played out in the construction of a figured world of “schooled mathematics.” We argue that the consequences that necessarily follow from these common-sense assumptions construct mathematics as hierarchical and fixed, placing learners on a one-dimensional learning trajectory.  Finally, we locate this set of emergent assumptions in the neoliberal racial project and consider the ways in which they shape a particular imagination of schooling and mathematics under neoliberalism.